Analisis Implementasi Indeks Desa Berbasis Aplikasi Web untuk Pendataan dan Pemantauan Pembangunan di Desa Keper, Kecamatan Krembung - Alfiatus Fadjar Kurnaini; Ilmi Usrotin Choiriyah (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to analyze the implementation of the Village Index Application in Keper Village, Krembung District, Sidoarjo Regency, as a new instrument for data collection and monitoring of village development following the enactment of Ministerial Regulation of Villages, Development of Disadvantaged Regions, and Transmigration (Permendesa PDTT) Number 9 of 2024. This research is important because there remains a gap between the adoption of digital systems and the capacity of village officials to manage them. The study employed a descriptive qualitative method using Charles O. Jones’ implementation theory, which includes the dimensions of organization, interpretation, and application. Data were collected through interviews, observations, and documentation. The results show that the application was implemented effectively despite limitations in human resources and technical constraints. In terms of organization, vacant positions caused overlapping duties; however, coordination among village officials remained functional. In terms of interpretation, socialization and technical guidance improved policy comprehension, although the interpretation was still administrative in nature. In terms of application, implementation followed the 2025 Village Index Data Collection SOP and achieved a score of 83.17, classifying Keper Village as an Independent Village. These findings confirm that the Village Index Application is effective as a tool for monitoring village development, providing practical contributions to strengthening human resource capacity, optimizing digital infrastructure, and ensuring continuous technical assistance, while also enriching theoretical studies on technology-based public policy implementation at the Village level.